Analisis Faktor Kesulitan Belajar Biologi Siswa Materi Bioteknologi di SMA Negeri Se-Kota Medan - Wahida Rahmadani; Fauziyah Harahap; Tumiur Gultom (Magister Pendidikan Biologi, Universitas Negeri Medan, 2017)
The aim of the study is to determine students’ learning difficulties at all Public Senior High School (SMA) in Medan. This research is descriptive. The population of the study is all students of class XII totaling 7272 in 21 Public Senior High Schools (SMA Negeri) spread over 15 districts. Samples were taken using Purposive Sampling, they are 524 students of class XII in 7 schools. The techniques for data collection use questionnaires of students’ learning difficulties and interviews. The finding of the study concluded that factors caused the biggest students’ learning difficulties derived from external factors (44%), which consist of laboratories factor (49%), books (45%) and the teacher factor (37%). The percentage of internal factors was (43%), which consist of the talent factor (50%), interest (44%) and motivational factors (36%).